PENINGKATAN PENGETAHUAN MASYARAKAT KELURAHAN SUKARASA, KECAMATAN SUKASARI, KOTA BANDUNG DALAM PEMBUATAN KOMPOS DENGAN METODE TAKAKURA (Poltekkes Kemenkes Bandung, 2023)
Sukarasa Village, Bandung City is a densely populated area with many community activities carried out in the neighborhood so that waste production continues and there is no proper waste management in the area. The purpose of this community service activity is to find out changes in knowledge and making compost using the Takakura method. This community empowerment activity was carried out by providing materials and demonstrations to the residents of RW 02 and RW 03, Sukarasa Village, Sukasari District, Bandung City. This community service resulted in residents' knowledge about making compost using the Takakura method, which increased from only 30% pre-test to 70% in the post-test. Compost is the result of composting using the Takakura method resulting in an average waste weight reduction of 53.66%. Organic materials that experienced the highest weight loss were mustard greens, dried leaves and carrots. This activity can effectively increase residents' knowledge about making compost using the Takakura method.